Attosecond charge migration and its laser control. (August 2015) - Kraus, P M; Mignolet, B; Baykusheva, D; Rupenyan, A; Horný, L; Penka, E F; Tolstikhin, O I; Schneider, J; Jensen, F; Madsen, L B; Bandrauk, A D; Remacle, F; et al.
Synopsis: We advance high-harmonic spectroscopy to resolve molecular charge migration in time and space and simultaneously demonstrate extensive control over the process. A multidimensional approach enables us to reconstruct both quantum amplitudes and phases with a resolution of better than 100 attoseconds and to separately reconstruct field-free and laser- driven charge migration. Our techniques make charge migration in molecules measurable on the attosecond time scale and open new avenues for laser control of electronic primary processes.